Problematic social media use and mental health risks among first-year Chinese undergraduates: a three-wave longitudinal study - Zhou, Wanqi; Yan, Zhihao; Yang, Zeyang; Hussain, Zaheer (Frontiers in Psychiatry, 2023)
The association between social media use and mental health risks has been widely investigated over the past two decades with many cross-sectional studies reporting that problematic social media use (PSMU) is associated with higher mental health risk such as anxiety and depression. The present study examined the relationship between PSMU severity and mental health risks (depression, anxiety, stress, and loneliness) using a three-wave longitudinal design. A total of 685 first-year Chinese undergraduate students (Mean age = 19.12 years, SD = .92) completed surveys at three times points with intervals of three to four months. Results revealed that PSMU was positively correlated with all the mental health risk variables over the three time points. The prevalence of PSMU increased over the three research waves. Cross-lagged models identified bidirectional relationships between PSMU and mental health risks, while such links were not consistent between different mental health risk variables and can change over different research intervals. This study indicates that PSMU and mental health risks could predict each other in a vicious loop, but the differences between specific mental health risks and the research context (e.g., different term times and experiences in university) should not be ignored. Further research attention should be paid to the prevalence of PSMU and mental health conditions among Chinese first-year undergraduates who appear to have difficulties in adapting to university life.